"You are only as healthy as your neighbour": collective vulnerability and (un)ethical responsiveness to the early phases of the pandemic in Palestine. Issue 3 (27th May 2021) - Hamamra, Bilal; Uebel, Michael; Abu Samra, Sanaa
ABSTRACT: Drawing upon Judith Butler's conceptualization of vulnerability, precariousness and precarity, this paper sheds light on the ontological foundation of the vulnerable human condition during the outbreak of the pandemic. While inspiring examples of cooperation among nations during the pandemic bring to the fore a transnational ethics of respect for differences, the pandemic turns out to be the unfortunate breeding ground for confrontation among some nations, highlighting an abdication of ethical responses that the vulnerability of proximate others demands. In this paper we look at the case of Palestine, examining how the solidarity of the Palestinian people to respond to the pandemic is imperiled by the Israeli occupation. The Israeli occupation, we contend, disavows vulnerability and the ethical response it entails, where the crisis of the pandemic serves as a revealing context for oppression of the Palestinians who exist under the threat of displacement and the annexation of the West Bank.